Antepartum Hemorrhage and Outcome of Very Low Birth Weight, Very Preterm Infants: A Population-Based Study - Klinger, Gil; Bromiker, Reuben; Zaslavsky-Paltiel, Inna; Sokolover, Nir; Lerner-Geva, Liat; Yogev, Yariv; Reichman, Brian; in collaboration with the Israel Neonatal Network (American Journal of Perinatology, 2020)
Objective We aimed to determine the independent effect of maternal antepartum hemorrhage (APH) on mortality and major neonatal morbidities among very low birth weight (VLBW), very preterm infants.Study Design A population-based cohort study of VLBW singleton infants born at 24 to 31 weeks of gestation between 1995 and 2016 was performed. Infants born with the following pregnancy associated complications were excluded: maternal hypertensive disorders, prolonged rupture of membranes, amnionitis, maternal diabetes, and small for gestational age. APH included hemorrhage due to either placenta previa or placental abruption. Univariate and multivariable logistic regression analyses were performed to assess the effect of maternal APH on mortality and major neonatal morbidities.Results The initial cohort included 33,627 VLBW infants. Following exclusions, the final study population comprised 6,235 infants of whom 2,006 (32.2%) were born following APH and 4,229 (67.8%) without APH. In the APH versus no APH group, there were higher rates of extreme prematurity (24–27 weeks of gestation; 51.6% vs. 45.3%, p < 0.0001), mortality (20.2 vs. 18.5%, p = 0.011), bronchopulmonary dysplasia (BPD, 16.1 vs. 13.0%, p = 0.004) and death or adverse neurologic outcome (37.4 vs. 34.5%, p = 0.03). In the multivariable analyses, APH was associated with significantly increased odds ratio (OR) for BPD in the extremely preterm infants (OR: 1.31, 95% confidence interval: 1.05–1.65). The OR's for mortality, adverse neurological outcomes, and death or adverse neurological outcome were not significantly increased in the APH group.Conclusion Among singleton, very preterm VLBW infants, maternal APH was associated with increased odds for BPD only in extremely premature infants, but was not associated with excess mortality or adverse neonatal neurological outcomes.Key Points
Keywords: very low birth weight; preterm infants; antepartum hemorrhage; mortality; neonatal outcome